Differential effects of ocean acidification on growth and photosynthesis among phylotypes of Symbiodinium (Dinophyceae) - Brading, P; Warner, ME; Davey, P; Smith, DJ; Achterberg, EP; Suggett, DJ (2011)
We investigated the effect of elevated partial pressure of CO2 (pCO2) on the photosynthesis and growth of four phylotypes (ITS2 types A1, A13, A2, and B1) from the genus Symbiodinium, a diverse dinoflagellate group that is important, both free-living and in symbiosis, for the viability of cnidarians and is thus a potentially important model dinoflagellate group. The response of Symbiodinium to an elevated pCO2 was phylotype-specific. Phylotypes A1 and B1 were largely unaffected by a doubling in pCO2; in contrast, the growth rate of A13 and the photosynthetic capacity of A2 both increased by ~ 60%. In no case was there an effect of ocean acidification (OA) upon respiration (dark- or light-dependent) for any of the phylotypes examined. Our observations suggest that OA might preferentially select among free-living populations of Symbiodinium, with implications for future symbioses that rely on algal acquisition from the environment (i.e., horizontal transmission). Furthermore, the carbon environment within the host could differentially affect the physiology of different Symbiodinium phylotypes. The range of responses we observed also highlights that the choice of species is an important consideration in OA research and that further investigation across phylogenetic diversity, for both the direction of effect and the underlying mechanism(s) involved, is warranted. © 2011, by the American Society of Limnology and Oceanography, Inc.